IGF-1 Increases with Hyperbaric Oxygen Therapy and Promotes Wound Healing in Diabetic Foot Ulcers - Figen Aydin; Ahmet Kaya; Levent Karapinar; Mert Kumbaraci; Ahmet Imerci; Hasan Karapinar; Cengiz Karakuzu; Mustafa Incesu (Journal of Diabetes Research)
Objectives. To investigate insulin-like growth factor I (IGF-1) levels in response to hyperbaric oxygen therapy (HBOT) for diabetic foot ulcers and to determine whether IGF-1 is a predictive indicator of wound healing in patients with diabetic foot ulcers. Design and Methods. We treated 48 consecutive patients with diabetic foot ulcers with HBOT. Alterations of IGF-1 levels in patients whose wound healed with HBOT were compared with those in patients who did not benefit from HBOT. Results. There was no significant difference in initial IGF-1 levels between the two groups (P=0.399). The mean IGF-1 level increased with HBOT (P<0.05). In the healed group, the mean IGF-1 increase and the final values were significantly higher (P<0.05). In the nonhealed group, the mean IGF-1 increase was minus and the final values were not significantly different (P<0.05). The increase in IGF-1 level with HBOT was significantly higher in the healed group (P<0.001). Conclusions. IGF-1 increased significantly in the healed group. We believe that HBOT is effective in the treatment of diabetic foot ulcers, with an elevation of IGF-1. This alteration seems to be a predictive factor for wound healing in diabetic foot ulcers treated with HBOT.